Assessment of Mycobacterium Tuberculosis drug-resistance patterns in a public hospital of Lima, Peru during 2022: Evaluación de los patrones de farmacorresistencia de Mycobacterium Tuberculosis en un hospital público de Lima, Perú durante 2022 - Mosqueira Sanchez, Jorge Roberto (2023)
Background. Tuberculosis is a public health problem considered to be the world's leading cause of death from an infectious disease among adults. Diagnosis is often challenging and is based on clinical, epidemiological, radiological, bacteriological, histological and biochemical findings. Timely diagnosis, identification of the susceptibility profile and follow-up compliance is important to enable more effective treatment and avoid severe forms of the disease. Aim. Describe the resistance patterns of Mycobacterium tuberculosis identified in the period of the year 2022 at Hospital María Auxiliadora. Material and Methods. This is an observational, cross-sectional study of patients diagnosed with tuberculosis throughout the year 2022 in the Tuberculosis Center of Excellence (TB COE), division of the respiratory medicine department at the Hospital Maria Auxiliadora, Lima, Peru. Data was collected from the medical records which was then included for the statistical analysis. The clinical and demographic characteristics were described by absolute frequencies and percentages. Chi-square test and Fisher's exact test were used to evaluate the association between the sensitivity profile of tuberculosis and the independent variables. A p-value < 0.05 was considered as statistically significant. Results. A total of 261 medical records were included in the present study. The most frequent age group was 17-59 years old, the majority were male (62.1%) and 15.7% were relapses, as established on national technical standard. Of the total, 89.7% were sensitive to first line drugs; 6.1% of the patients were multidrug-resistant (MDR), and 0.8% presented extensively drug-resistance (XDR); likewise, 0.8% and 2.7% presented resistance for rifampicin only and resistance for isoniazid only respectively. HIV infection was found at 14.2%. The most common form of tuberculosis was pulmonary (49%) followed by pleural tuberculosis (21.8%). Conclusion. Tuberculosis is a worldwide condition whose drug-resistance patterns continue evolving. However, in our hospital, a southern Peru reference Center, most TB patients are still sensitive to first line drugs. Only a small amount of MDR and XDR patients were found. Moreover, the most common clinical presentation was pulmonary followed by pleural tuberculosis.